(untitled) (Research, Society and Development, 2022)
Uprighting inclined molars, whether due to anodontics or premature loss of adjacent teeth, can be a challenge for orthodontists. There are many mechanics used to correct this inclination, but it is necessary to analyze the side effects that can be caused during the verticalization process. The present work deals with a case report where a root correction loop was chosen, activated in the VI geometry and associated with a mini inverted thread bracket head screw, a mechanic that brings a minimum of unwanted side effects.